FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU: LITERATURE REVIEW - Hidayatulloh; Mumtaz, Shafira; Rindanigsih, Ida (Antis Publisher, 2023)
This study aims to obtain a theoretical basis that can support solving the problem being studied on the effect of motivation and work stress on teacher performance. The theory obtainer is the first step so that researchers can better understand the problemed being researched correctly according to a scientific framework. The method used in this research is a literature review. Researchers select the feasibility of research articles based on the background of the article, research methods, discussed results, discussion and conclusions. In this study, the data source used is secondary data sources. An article search was carried out via the lens.org website to conduct a literature search with the keywords